Representation of Authoritarian Parenting in the Korean Drama "The Good Bad Mother" - Novianti Arman; Hastuti Hastuti; Muh. Rizal Ardiansah Putra (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study examines the impact of authoritarian parenting in the drama "The Good Bad Mother." The research employs a qualitative method using Ferdinand De Saussure's semiotic analysis, where Ferdinand divides signs into two components: the signifier and the signified. The drama tells the story of a single mother who is strict with her child, especially regarding education, resulting in Kang-ho becoming a successful prosecutor. However, as a prosecutor, Kang-ho becomes cold-hearted. The findings, gathered through documentation and observation of the film's scenes, reveal several impacts on the child resulting from the parent's authoritarian parenting style. It was found that children who experience authoritarian parenting tend to feel more negative effects compared to positive ones from this style of upbringing.